The economic costs of hoarding behaviours in local authority/housing association tenants and private home owners in the north-east of England. (July 2017) - Neave, N.; Caiazza, R.; Hamilton, C.; McInnes, L.; Saxton, T.K.; Deary, V.; Wood, M.
Highlights: We assessed the incidence of hoarding behaviours in private and Housing Association tenants in the North-East of England. We assessed the economic costs to Local Authorities and Emergency Services. While hoarders comprise a small proportion of the population, the economic and social costs of dealing with their behaviours are high.